Sistem Pakar Diagnosa Penyakit Tanaman Cabai Rawit Dengan Metode Inferensi Forward Chaining - Tri Handayani; Febrina Sari; Abdul Jalil (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Chilli as one of the commodity which have never been left by Indonesia society, can be said that bt cilli have become the part of Indonesia people culture, but metter which often happened many chilli crop which is dead to be resulted caused by overdue disease for the diagnosis of consultancy to is expert of cilli crop represent correct choice, but expert amount is environment on duty agriculture very limited. Metter that’s causing to fail loss ang crop which in experiencing of farmers.Writer try to perceive existing the root of the metter and try to give guidance to all farmers for using a information technology in the form of expert system as one the way of to handle the problem of which is farmers. Method tobe used by that is method of forward chaining, conducting scheme of prosess model use model of DFD, scheme of database, scheme of relationship and interface between table.Application at this research that is expert system of diagnosis disease of cayenne crop, Using a rule base (rule-based) using a forward chaining inference method that is intended to help farmers in diagnosing diseases of cayenne crop. Expected cayenne crop diagnosis expert system using a forward chaining, it could be a tool for farmers in their cayenne crop disease diagnosis.Keywords : expert system, diagnosis, forward chaining.